(untitled) (Ameghiniana, 2014)
"Faunal differences in the uppermost part (Lower Llanvirnian) of the San Juan Formation are discussed on the basis of sponge and brachiopod associations collected from four localities of the Precordillera basin (cerro Viejo, cerro La Chilca, Talacasto, and sierra de Villicum). Data on their relative abundance are presented in percent biovolume that provides a more valuable information than the number of specimens. From an autecological viewpoint two morphological types of sponges can be recognized: discoidal and elongate. Genera of brachiopods can be grouped in three life strategies: pedunculate, quasi-infaunal, and liberosessil. The distribution of biovolume data of both sponges and brachiopods, suggests that the energy regime and the substratum conditions are the physical limiting factors inducing faunal differences. These factors are linked to a bathymetric profile, with a subtidal, shallow water area in the southern part (Talacasto- Villicum region) and a deeper, probably below wave base water, near the cerro Viejo locality. The northward deepening of the basin probably reflects the rapid subsidence due to active deformational loading during early phases of the Guandacol orogeny."